Vision and genesis of survival strategies in tsetse flies: A laboratory study. (May 2018) - Mebourou, Emmanuel Kamba; Bernáth, Balázs; Schenker, Dominique; Guerin, Patrick M.
Graphical abstract: Highlights: Apart from taking a blood-meal, tsetse spend most of their lives in the shade. In this manner diurnal tsetse control metabolic rate and avoid predation. We show how tsetse can fly to perches off the ground in almost complete darkness. Mature tsetse can discriminate between bars of 1 and 2 cm in diameter in the dark. Optomotor and retinogram recordings indicate higher visual acuity in mature tsetse. Abstract: Organisms respond to environmental stimuli in ways that optimize survival and reproduction. Tsetse fly life-history is characterized by high investment in progeny by the pregnant female and low birth rate. This places constraints on tsetse populations across the sub-Saharan biotopes they colonize where extreme climatic conditions militate against survival. Controlling metabolic rate is crucial in biotopes where daily swings in temperature can exceed 20 °C. Tsetse acquire their nutrient requirements from the blood meal. These diurnal flies are otherwise confined for most of their lives to perching sites in the shade. At these locations they are simultaneously threatened by vertebrate and invertebrate predators. Here we describe behaviours of the East African tsetse Glossina pallidipes Austen (Diptera: Glossinidae) that permit it to reduce risk daily. Newly-emerged flies remain immobile at emergence in the photophase but scotophase-emerging flies walk away within seconds to climb (negative geotaxis) vertical substrates to find a perch off the ground. Flies of all ages show the ability to fly in almost total darkness (1.10 −5  lux) in the scotophase to perch on the upper side of horizontally suspended 1 cm diameter bars, simulating branches of vegetation, but perch under the same bars during the photophase. This underlines the predilection of tsetse for objects with a linear aspect that provide a vantage point and shade. Mature G. pallidipes can discriminate between horizontally suspended bars of different diameter and shape. Flicker fusion frequency values established by optomotor and retinogram recordings reveal a higher visual acuity in mature compared to newly-emerged tsetse.